A study on nutritional status of adolescent girls of Dongria Kondh tribe - Nanda, Sikata; Dhar, Rabi Narayan (International Journal Of Community Medicine And Public Health, 2017)
Background: Nutritional status of adolescent girls are different from the younger children and older adults. In the tribal population they are more neglected in comparison to boys because of limited resources and health care facilities. In the present study we have done assessment of nutritional status of adolescent girls in the Dongria Kondh tribe in Odisha. Methods: Dongria Kondh’ residing in Rayagada district of Odisha, having its maximum concentration was studied. Bissam Cuttack block was selected randomly as the study area. Moreover, coincidently majority of the study population resided in the block having villages like Kurli, Khambesi, Hundijali, Muthesi, Khajuri, Mundabali and Uppar Gandatallli which are situated as a distance of 5000 ft height above sea level. 89 adolescent girls were considered to assess the nutritional status of tribal adolescent girls of Dongria Kondh tribe to study the different factors associated with the nutritional status of the girls and to suggest remedial measures for integrated development of the adolescent girls. Results: Most of the girls (81%) were from nuclear family. All girls belonged to low socio economic status. The energy intake was adequate only in 35% of study subjects. The protein intake was adequate in only 38% of study subjects. The common types of food consumed was rice, ragi and seasonal fruits and all were non vegetarian. Conclusions: The widespread problem of poverty, illiteracy, malnutrition, absence of sanitary living condition, ignorance of cause of disease still are the contributing factors for the deplorable condition prevailing amongst the adolescent girls of the tribal group. As they are future mothers, improvement of nutritional status should be the primary objective.